PENGARUH PENERAPAN MODEL PEMBELAJARAN COOPERATIVE TIPE STUDENT TEAMS ACHIEVEMENT DIVISION ( STAD ) TERHADAP HASIL BELAJAR TEKNIK ELEKTRONIKA DASAR DI SMK NEGERI 2 PAYAKUMBUH - Andre Devid; Delsina Faiza; Edidas Edidas (Universitas Negeri Padang, 2017)
This research was focusing on the low of student’s learning outcome, specially on Basic Electronics subject at SMKN 2 Payakumbuh. The subjective is to reveal the effect of applying Student Teams Achievement Division (STAD) learning model to the subject. By using Quasi experimental with simple random sampling; one of probability sampling tecnique, the model was enducted in experiment class. A control class where Problem Based Learning (PBL) learning model, was also implemented to compare the treatment. The primary data was measured by structured test (Post-test) according to basic competences described of the subject based on the t-test result, complying the pre-requisite test such as normalityexamination, this research found that t>t0 (2,48 > 2.01). This proves that there are significant differences in student learning outcomes using cooperative learning model type Students Teams Achievement Divisions (STAD) with Scientific approach of Problem Based Learning type in subjects of Basic Electronics Technique class X Audio Technique Video at SMKN 2 Payakumbuh.Keywords : Student Teams Achievement Division (STAD, Problem Based Learning (PBL) learning model, learning outcomes, learning model.